Management of severe gastrointestinal tuberculosis with injectable antituberculous drugs - Goldani, Luciano Zubaran (2015)
Abstract: Abdominal tuberculosis (TB) is generally responsive to medical treatment, and early diagnosis and management can prevent unnecessary surgical intervention. However, intravenous therapy is needed for severe forms of tuberculosis with extensive gastrointestinal involvement. The authors report an immunocompetent patient with gastrointestinal TB who was successfully managed with a combination of surgical intervention and anti-TB medications, and discuss the importance of injectable anti-TB medications in the management of severe gastrointestinal TB. The present case report provides a model for assessment and intervention in severe forms of gastrointestinal TB.